Analisis Minat Penggunaan Transportasi Online Maxim pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang - Dina Afrilya; Efriyani Sumastuti; Rita Meiriyanti (Jurnal Simki Economic, 2024)
This research aims to test hypotheses and explain phenomena in the form of relationships between variables, namely brand image, price, word of mouth, brand trust, and service quality on interest in using Maxim online transportation among students at the Faculty of Economics and Business, PGRI University Semarang. This research uses a quantitative approach method. The data analysis technique used in this research is multiple linear regression with testing using SPSS. The test results show that brand image and price have no influence on interest in using Maxim online transportation. Word of mouth, brand trust, and service quality have a significant positive influence. Brand image, price, word of mouth, brand trust, and service quality simultaneously influence positively and significantly. The importance of managing and improving a number of aspects in creating a positive and enjoyable image for users. The positive influence of this combination of variables can indicate the existence of a mutually reinforcing interaction or relationship between the variables.